Bengkulu Brovape Promotion Strategy in Attracting Consumer Buying Interest (Study of Marketing Communication Strategy at Brovape Stores in Bengkulu) - Ivan Satria Negara; Dedi Supriyadi; Yudisani Yudisani (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
The title of this research is "Bengkong Brovape Promotion Strategy in Attracting Consumers Buying Interest (Study of Marketing Communication Strategy at Brovape Stores in Bengkulu)". The purpose of this study was to determine the promotion strategy of Brovape Bengkulu in attracting consumer buying interest. This study uses descriptive qualitative research methods with data collection techniques participant observation, in-depth interviews, and documentation. The results of this study indicate that the promotional strategy carried out by Brovape Bengkulu in attracting consumer buying interest with 2 forms of strategy, namely the first strategy by way of sales promotion by cutting prices, holding giveaway events and holding door prizes and explaining the product in detail to consumers, by In this way, consumers become interested in buying existing products and consumers will invite their friends to shop at the Brovape Bengkulu store. The second strategy is by way of advertising that uses social media where social media is a medium that is often used by consumers so that consumers know what products are in Brovape Bengkulu by using pictures and explanations without consumers coming to the Bengkulu Brovape store in this way consumers will pay attention and can make a decision to buy products at the Bengkulu Brovape store. Thus the sales of the Bengkulu Brovape store will increase. In analyzing the results of this study using the Aidda theory.